CORPORATE GOVERNANCE DAN PROFITABILITAS: PERAN BIAYA MODAL SEBAGAI VARIABEL MEDIASI - Eka Febiyanti; Hersugondo Hersugondo (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of the internal mechanism of corporate governance consisting of the size of the board of directors and the size of the board of commissioners empirically on profitability as measured by return on assets (ROA). This study uses the cost of capital to be tested as a mediating variable between the independent and dependent variables. The study used companies listed on the Indonesia Stock Exchange during the period 2015 to 2020.This study uses secondary data collected from Bloomberg financial data and the company's annual report. A total of 807 companies as a population by sampling with purposive sampling method in order to obtain 300 companies from various sectors. This research combines time series data with cross section. The analysis method uses multiple regression analysis and path analysis to see the influence between the independent and dependent variables and the role of the mediating variable. Based on the hypothesis testing regression analysis, the research results show that corporate governance which consists of the size of the board of directors has a significant negative effect on the cost of capital and the size of the board of commissioners has a positive and insignificant effect on the cost of capital. The cost of capital has no significant positive effect on ROA while the size of the board of directors and commissioners has a positive and significant effect on ROA. Then the cost of capital cannot mediate the effect of the size of the board of directors and the size of the board of commissioners on the company's profitability as measured by return on assets (ROA).